Hubungan Antara Religiusitas Dengan Kecemasan Menghadapi Pernikahan - Haq, Fajrul, Aad Satria Permadi, S.Psi, MA (2016)
Phenomenon Happens When Cantor is the number of women and men in the age Enough And Living Conditions established yet Reluctant to review Married BECAUSE different reasons. Only one woman is interest in career field compared ON WITH Married. * According to the happiness index BPS The dikelurkan By 2014, showed that the population The status Unmarried happy Slightly MORE Than they Are Already Married. Happiness index is formulated based on the Ten Aspects of Life that Works, household income, housing conditions and assets, education, health, family harmony, social relations, the availability of leisure time, the state Environmental and Safety Conditions. Singer study aims to review Seeing Relations eligiosity BETWEEN THE Facing wedding anxiety. Population Research Singer is an adult male orangutan And Women Who are single, aged 19 Years To 40 Years, Muslim and work. Sampling Techniques Used Research hearts That singer is purposive sampling sampling techniques based on differences such as A Certain Consideration Qualities or haracteristics of the population is well known in advance. Timeframe The samples taken for a review of research singer is as much as 100. That data collection methods you anxiety and religiosity scale. Based on the findings of the analysis of IN oefficient (r) of -0398 WITH p = 0.000 (p <0.01). It Means Singer hypothesis The proposed ADA Writer Proven That The Very significant negative relationship between religiosity anxiety Facing wedding. Effective contribution of 15.9% of religiosity variable Against Confronting anxiety marriage. There are still 84.1% mean lying variables affecting the wedding Confronting anxiety. Facing the unknown variable anxiety empirical wedding had a mean of 43.58 and a mean of 69 Which Means hypothetical ON classified study subjects was low. CONCLUSION The TIN IN Research Singer is a negative correlation between religiosity WITH anxiety Facing wedding.